Successful management of ruptured ovarian ectopic pregnancy: a case report - Chandel, Anu; Gupta, Chanchal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Ovarian pregnancy is one of the rarest sites of non-tubal ectopic pregnancy. It has a prevalence of 0.5-3.5% in all ectopic pregnancies. It usually presents with rupture in the first trimester, a potential life-threatening condition. A preoperative diagnosis is difficult to make. Majority of the cases are diagnosed intraoperatively followed by confirmation on histopathology. We presented a case of 32-year-old woman with previous two normal deliveries at 7 weeks gestation who presented with abdominal pain and spotting. She was diagnosed with ruptured ovarian ectopic pregnancy on laparotomy and salpingo-oophorectomy was done. Later, ovarian pregnancy was confirmed on histopathology. The incidence of ovarian ectopic pregnancy is increasing and it should be considered as a differential diagnosis in women of childbearing age coming to emergency department with abdominal pain. It is important to keep a high index of suspicion for its diagnosis. High resolution transvaginal ultrasonography can help in earlier detection and preventing some of its complications like rupture, shock and maternal mortality.